Splenic infarction as a rare complication of infectious mononucleosis due to Epstein–Barr virus infection in a patient with no significant comorbidity: Case report and review of the literature. (November 2013) - Gavriilaki, Eleni; Sabanis, Nikolaos; Paschou, Eleni; Grigoriadis, Savas; Mainou, Maria; Gaitanaki, Alexandra; Skargani-Koraka, Maria
Abstract We report the case of a 17-y-old boy diagnosed with infectious mononucleosis due to Epstein–Barr virus infection who complained of left upper quadrant pain. A magnetic resonance imaging scan showed a splenic infarct in the enlarged spleen. Other causes of splenic infarction were excluded. Thus, infectious mononucleosis may cause splenic infarction in patients without other comorbidities.